234k views
3 votes
Consider the sequence of steps to solve the equation: 2(x - 4) + 6x = 9x - 10

Given = 2(x - 4) + 6x = 9x - 10
Step 1 = 2x - 8 + 6x = 9x - 10
Step 2 = 2x + 6x – 8 = 9x - 10
Step 3 8x - 8 = 9x - 10
Step 4 = 8x - 8x - 8 = 9x – 8x - 10
Step 5 = 0 - 8 = x - 10
Step 6 = -8 = x - 10
Step 7 = -8 + 10 = x - 10 + 10
Step 8 = 2 = x + 0
Step 9 = 2 = x
Which step in solving this equation is justified by the Distributive Property?

User Musa Muaz
by
5.6k points

1 Answer

3 votes
step 1 because the 2 is multiplied by the (x-4)
User Michael Kolakowski
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.